Application of lipid nanoparticles to ocular drug delivery. (1st December 2016) - Battaglia, Luigi; Serpe, Loredana; Foglietta, Federica; Muntoni, Elisabetta; Gallarate, Marina; Del Pozo Rodriguez, Ana; Solinis, Maria Angeles
ABSTRACT: Introduction : Although eye drops are widely used as drug delivery systems for the anterior segment of the eye, they are also associated with poor drug bioavailability due to transient contact time and rapid washout by tearing. Moreover, effective drug delivery to the posterior segment of the eye is challenging, and alternative routes of administration (periocular and intravitreal) are generally needed, the blood–retinal barrier being the major obstacle to systemic drug delivery. Areas covered : Nanotechnology, and especially lipid nanoparticles, can improve the therapeutic efficiency, compliance and safety of ocular drugs, administered via different routes, to both the anterior and posterior segment of the eye. This review highlights the main ocular barriers to drug delivery, as well as the most common eye diseases suitable for pharmacological treatment in which lipid nanoparticles have proved efficacious as alternative delivery systems. Expert opinion : Lipid-based nanocarriers are among the most biocompatible and versatile means for ocular delivery. Mucoadhesion with consequent increase in pre-corneal retention time, and enhanced permeation due to cellular uptake by corneal epithelial cells, are the essential goals for topical lipid nanoparticle delivery. Gene delivery to the retina has shown very promising results after intravitreal administration of lipid nanoparticles as non-viral vectors.